(untitled) (Nepal Journal of Environmental Science, 2022)
The less biodegradable steroidal drug, Prednisolone is one of the widely used drugs in the treatment of autoimmune and infectious diseases. Transformation of prednisolone can be achieved with microbial activity. Isolation of prednisolone-resistant microorganisms was done using a sewage sample. Out of 5 isolates, one isolate was selected for further studies based on maximum tolerability to prednisolone. The isolate was identified based on MALDI-TOF. The strain was found to have a match score of 2.336 with gram-negative bacteria Klebsiella pneumoniae spp pneumoniae DSM3010 4T HAM. The isolate was found to degrade 80% prednisolone on the 5th day of fermentation. The concentration of prednisolone was determined using a colorimetric-based method and HPLC technique.